ORGANİK ATIKTAN HİDROTERMAL YÖNTEM İLE AKTİF KARBON SENTEZİ VE KARAKTERİZASYONU - TOKGÖZ, GÖZDE (Fırat Üniveristesi, 2025)
Günümüzde artan çevre sorunları ve sürdürülebilir malzeme üretimi ihtiyacı, tarımsal atıkların değerlendirilmesini önemli bir araştırma konusu haline getirmiştir. Özellikle yüksek karbon içeriğine sahip tarımsal atıkların, endüstriyel uygulamalarda yaygın kullanım alanı bulan aktif karbona dönüştürülmesi, hem atık yönetimi hem de ekonomik açıdan büyük önem taşımaktadır. Çalışmamızda organik bir atık olan, kayısı çekirdeği kabuğundan hidrotermal karbonizasyon yöntemi kullanılarak aktif karbon üretimi gerçekleştirilmiştir. Kayısı çekirdeği kabukları öğütülerek toz haline getirilmiş ve hidrotermal reaksiyon için hazırlanmıştır. Hidrotermal karbonizasyon işlemi, 240°C, 260°C ve 300°C olmak üzere üç farklı sıcaklıkta, 10 Bar basınç altında ve 24 saat süreyle gerçekleştirilmiştir. Elde edilen hidrokömürler daha sonra potasyum hidroksit (KOH) ile aktive edilmiş ve 700°C'de inert atmosfer altında ısıl işleme tabi tutulmuştur. Üretilen hidrokömür ve aktif karbon örneklerinin özelliklerini belirlemek için, Brunauer-Emmett-Teller (BET) yüzey alanı ölçümü, Taramalı Elektron Mikroskobu-Enerji Dağılımlı X-ışını Spektroskopisi (SEM-EDS), X-Işını Kırınımı (XRD) ve Fourier Dönüşümlü Kızılötesi Spektroskopisi (FTIR) analizleri gerçekleştirilmiştir. BET analiz sonuçlarına göre, başlangıçta 6,752 m²/g olan yüzey alanı, hidrotermal karbonizasyon sonrası artış göstermiş ve KOH aktivasyonu sonrasında 658,5564 m²/g'a kadar yükselmiştir. SEM görüntüleri, aktivasyon işlemi sonrasında mikro ve mezo gözeneklerin oluştuğunu ve yüzey morfolojisinin önemli ölçüde değiştiğini göstermiştir. EDS analizleri, işlemler sonucunda karbon içeriğinin arttığını ve başlangıçta %59,83 olan karbon oranının aktivasyon sonrası %85'in üzerine çıktığını ortaya koymuştur.

Today's increasing environmental problems and the need for sustainable material production have made the utilization of agricultural wastes an important research topic. The conversion of agricultural wastes with high carbon content into activated carbon, which is widely used in industrial applications, carries great importance in terms of both waste management and economic aspects. In our study, active carbon production was carried out using hydrothermal carbonization method from apricot kernel shell, which is an organic waste. The apricot kernel shells were powdered and prepared for the hydrothermal reaction. The hydrothermal carbonization process was carried out at three different temperatures of 240°C, 260°C, and 300°C, under 10 Bar pressure for 24 hours. The obtained hydro chars were then activated with potassium hydroxide (KOH) and subjected to heat treatment under inert atmosphere at 700°C. To determine the properties of the produced hydrochar and activated carbon samples, analyses such as Brunauer-Emmett-Teller (BET) surface area measurement, Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDS), X-ray Diffraction (XRD), and Fourier Transform Infrared Spectroscopy (FTIR) were performed. According to BET analysis results, the surface area, which was initially 6.752 m²/g, increased after hydrothermal carbonization and rose up to 658.5564 m²/g after KOH activation. SEM images showed that micro and meso pores were formed after the activation process and the surface morphology changed significantly. EDS analyses revealed that the carbon content increased as a result of the processes, and the carbon ratio, which was initially 59.83%, increased above 85% after activation. The study demonstrated that apricot kernel shell could be successfully converted into activated carbon with high surface area through hydrothermal carbonization and KOH activation. The results offer valuable insights into the conversion of agricultural waste into high-value materials and the production of sustainable resources.
Synthesis and characterisation of activated carbon from organic waste by hydrothermal method
Keywords: Metalurji Mühendisliği